👤

rozwiąż równanie
a) 3(x + 3) = 2(x +4) + x +1
b) 2x - 4 - 3(2 - x_ = 5(2x - 1)
c) 5(x + 4) - (2x - 3) = 2(2(1 - 2x)
d) 4(x - 2) - 2(x - 4) = 5(x +1) - 3x
e) 6x -(4x +5) = 2(x-2) - 1
f) 4(3x + 2) + 5(2x + 3) =-(2x + 13)


Odpowiedź :

Odpowiedź:

[tex]a)\\\\3(x+3)=2(x+4)+x+1\\\\3x+9=2x+8+x+1\\\\3x+9=3x+9\\\\3x-3x=9-9\\\\0=0[/tex]

Równanie tożsamościowe ma nieskończenie wiele rozwiązań

[tex]b)\\\\2x-4-3(2-x)=5(2x-1)\\\\2x-4-6+3x=10x-5\\\\5x-10=10x-5\\\\5x-10x=-5+10\\\\-5x=5\ \ /:(-5)\\\\x=-1\\\\\\c)\\\\5(x+4)-(2x-3)=2(1-2x)\\\\5x+20-2x+3=2-4x\\\\3x+23=2-4x\\\\3x+4x=2-23\\\\7x=-21\ \ /:7\\\\x=-3[/tex]

[tex]d)\\\\4(x-2)-2(x-4)=5(x+1)-3x\\\\4x-8-2x+8=5x+5-3x\\\\2x=2x+5\\\\2x-2x=5\\\\0=5[/tex]

Równanie sprzeczne nie ma rozwiązania

[tex]e)\\\\6x-(4x+5)=2(x-2)-1\\\\6x-4x-5=2x-4-1\\\\2x-5=2x-5\\\\2x-2x=-5+5\\\\0=0[/tex]

Równanie tożsamościowe ma nieskończenie wiele rozwiązań

[tex]f)\\\\4(3x+2)+5(2x+3)=-(2x+13)\\\\12x+8+10x+15=-2x-13\\\\22x+23=-2x-13\\\\22x+2x=-13-23\\\\24x=-36\ \ /:24\\\\x=-\frac{36}{24}\\\\x=-\frac{3}{2}\\\\x=-1\frac{1}{2}[/tex]